Policy Recommendations for the Administration of the Civil Defense Volunteer Center under Si Don Moon Sub-District Administrative Organization, Chiang Saen District, Chiang Rai Province - Nachan, Kwanchai; Chullasutti, Nualnapa; Imiwat, Prayoon (Journal of Public Administration Chiang Rai Rajabhat University, 2025)
The objectives of this study were: 1) to examine the problems and obstacles in the administration of the Civil Defense Volunteer Center under Si Don Moon Subdistrict Administrative Organization, Chiang Saen District, Chiang Rai Province; and 2) to develop policy recommendations for the management of the Civil Defense Volunteer Center under the Si Don Moon Subdistrict Administrative Organization, Chiang Saen District, Chiang Rai Province. For the first objective, a quantitative research method was employed. The population, selected through purposive sampling, consisted of 87 personnel. The data were analyzed for frequency, percentage, mean, and standard deviation. and a qualitative research method was used. Nine key informants were selected through purposive sampling including executives of the Si Don Moon Subdistrict Administrative Organization, heads of planning and administration from the Chiang Rai Provincial Disaster Prevention and Mitigation Office, assistant directors of the Civil Defense Volunteer Center, center staff, civil defense volunteers, village heads, and community representatives. The data were collected through focus group discussions. The results of the study found that 1) problems and obstacles in the administration of the Civil Defense Volunteer Center, Sri Don Moon Subdistrict Administrative Organization, Chiang Saen District, Chiang Rai Province the overall picture is at a moderate level. 2) Policy proposals for the administration of the Civil Defense Volunteer Center, Sri Don Muang Subdistrict Administrative Organization, Chiang Saen District, Chiang Rai Province. In terms of operational planning, it was found that should provide 2 percent of the population with volunteers and organize continuous training to develop volunteers. In terms of implementing the plan, it was found that should prioritize training in various forms of disaster prevention to continuously reduce the risk of disasters for the public. In terms of inspection or assessment, it was found that should assign personnel to perform routine tasks as a cycle to check readiness, prepare tools, equipment, and devices for disaster prevention and relief so that they can be operated immediately, and practice regularly. In terms of improvement and development, it was found that when the disaster is over, there should be a meeting to debrief specific groups immediately after the mission is completed (Hotwash), and there should be a debriefing of the overall organization again when the mission is completely completed (AAR).